Saksi Mahkota Dalam Pembuktian Tindak Pidana Korupsi: Perspektif Hukum Pembuktian Dan Asas Perlindungan Hak Terdakwa - Tiara Okta Yanti; Lidhya Agustini; Bella Syafirda; Dea Eryan Ananda; Ria Anggraeni Utami (GLOBAL SCIENTS PUBLISHER, 2025)
Corruption is an extraordinary crime with broad impacts on state budgets and public trust in officials, requiring efficient evidentiary methods. This study examines the role of crown witnesses in proving corruption crimes from the perspectives of evidentiary law and the protection of defendant rights. A normative juridical method using statutory and conceptual approaches through literature review was applied. The findings indicate that the use of crown witnesses is a legitimate extraordinary evidentiary tool if supported by other evidence and does not violate defendant rights. However, challenges include regulatory ambiguity, potential human rights violations, witness credibility, and witness protection. This study offers normative recommendations to balance evidentiary effectiveness and human rights protection in the criminal justice system.